2021
DOI: 10.1001/jamanetworkopen.2021.38983
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Contraceptive Use Among Immigrant Women Following Expansion of Medicaid Coverage for Postpartum Care

Abstract: IMPORTANCEAccess to postpartum care is restricted for low-income women who are recent or undocumented immigrants enrolled in Emergency Medicaid. OBJECTIVE To examine the association of a policy extending postpartum coverage to Emergency Medicaid recipients with attendance at postpartum visits and use of postpartum contraception. DESIGN, SETTING, AND PARTICIPANTS This cohort study linked Medicaid claims and birth certificate data from 2010 to 2019 to examine changes in postpartum care coverage on postpartum car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…For the full report, our electronic searches yielded 25 973 citations (Figure). We screened 589 full-text articles, of which 28 studies, reported in 29 articles, were eligible for the current systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the full report, our electronic searches yielded 25 973 citations (Figure). We screened 589 full-text articles, of which 28 studies, reported in 29 articles, were eligible for the current systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 2 studies evaluated the impact of policy changes that made insurance coverage less comprehensive: 1 study in North Carolina that evaluated a policy reducing reimbursement rates for maternity care coordination by 19% and 1 study in Oregon that evaluated a policy requiring undocumented immigrants and legal immigrants within 5 years of immigration with Emergency Medicaid who wanted sterilization following vaginal delivery to pay for it . Finally, 9 studies compared outcomes in various insurance expansion and nonexpansion (or contraction) states …”
Section: Resultsmentioning
confidence: 99%
“…Births were identified using International Classification of Disease, Ninth Revision and International Statistical Classification of Diseases and Related Health Problems, Tenth Revision codes as well as Current Procedural Terminology codes and using a previously published algorithm. 17 , 18 , 19 …”
Section: Methodsmentioning
confidence: 99%
“…We examined the use of any antidiabetic agent among pregnant patients with diabetes and the use of insulin alone, which is the first-line pharmacotherapy recommended for glycemic optimization during pregnancy. Births were identified using International Classification of Disease, Ninth Revision and International Statistical Classification of Diseases and Related Health Problems, Tenth Revision codes as well as Current Procedural Terminology codes and using a previously published algorithm …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation